RETRACTED: Forecast on 2030 Vietnam Electricity Consumption - Nguyen, V. H. M.; Nguyen, K. T. P.; Vo, C. V.; Phan, B. T. T. (Engineering, Technology & Applied Science Research, 2018)
This article has been retracted at the request of the Editor-in-Chief and the co-authors as the article is largely based on work presented previously by the same authors at an international conference. The conference paper is: H. M. V. Nguyen, T. P. K. Nguyen, V. V. Cuong and T. T. B. Phan, "Forecast on Vietnam electricity consumption to 2030," 2017 International Conference on Electrical Engineering and Informatics (ICELTICs), Banda Aceh, Indonesia, 2017, pp. 72-77, doi: 10.1109/ICELTICS.2017.8253238. The authors accept the retraction as they claim that their only and bona fide aim for publishing the retracted paper was to notify the research community that they had updated some of the data they had reported in the conference paper and were unaware of the erratum/addendum procedure that they should have followed then and wish to follow now.